Exploration of Salined Areas in the Mughan Plain on the Basis of Space Pictures - Meherremlı, Latafat (Київський національний університет імені Тараса Шевченка, 2021)
Aim: the main aim of the study is exploratıon of salıned areas ın the mughan plaın on the basıs of space pıctures. Methodology: The article is based on a study of saline areas in the Mugan plain. The study was conducted to compare the results of satellite imagery analysis with the actual situation in the area. As a result of the research, various cartographic maps of the area were compiled and evaluated. Results: The history of the formation of the plain provides a necessary opportunity to explain the accumulation of salts in one way or another in the soils of the area. The western gulf of the Caspian Sea, which existed before the fourth period, as a result of its transgression and regression, was undoubtedly a major factor in the salinization of the territory. Analysis of geological materials shows that the saline sediments in the mountain systems covering the plains of the republic are eroded by external and internal factors and brought to the less inclined areas of the area under the influence of surface and underground currents. Surface water refers mainly to water flowing from mountain slopes. In this case, both the amount and chemical composition of the imported salts, of course, depends, above all, on the salinity of the eroded rocks and their chemical composition, which in turn is closely linked to the geological history of the area. In low-slope areas, deluvial currents flowing to this part of the slopes increase the density of the solution by dissolving the salts found in the areas they pass through as they move along the surface. On the other hand, the density of streams moving inland from the upper parts of the slopes also increases here. In both cases, the deluvial currents flow to the ground in the less inclined part of the field, reducing their flow velocity. Finally, the solution soaked in the soil evaporates again in high-temperature climates, causing varying degrees of salinity, depending on the amount of salts it contains Scientific novelty: The obtained scientific results will enable the protection of the ecological diversity of landscapes on the plain of the Caspian Sea and optimize natural resource potential of landscapes.
Keywords: agrolandscape; ecosystem; salinization; emote sensing; analysis of satellite images; NDVI; LST